2017
DOI: 10.1136/bmjopen-2016-011547
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for admission at three urban emergency departments in England: a cross-sectional analysis of attendances over 1 month

Abstract: ObjectiveTo investigate factors associated with unscheduled admission following presentation to emergency departments (EDs) at three hospitals in England.Design and settingCross-sectional analysis of attendance data for patients from three urban EDs in England: a large teaching hospital and major trauma centre (site 1) and two district general hospitals (sites 2 and 3). Variables included patient age, gender, ethnicity, deprivation score, arrival date and time, arrival by ambulance or otherwise, a variety of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…The site for the study was a large urban teaching hospital (a major trauma centre with a hyperacute stroke unit), with an annual attendance volume of around 129 000i and an overall admission rate during the study period of 23% 22. The ED is consultant-staffed 24 hours a day, has 38 adult beds and a 14-bed CDU.…”
Section: Methodsmentioning
confidence: 99%
“…The site for the study was a large urban teaching hospital (a major trauma centre with a hyperacute stroke unit), with an annual attendance volume of around 129 000i and an overall admission rate during the study period of 23% 22. The ED is consultant-staffed 24 hours a day, has 38 adult beds and a 14-bed CDU.…”
Section: Methodsmentioning
confidence: 99%
“…was associated with higher transience factors to patients' presentation at the ED. In contrast, they found less influence of day of the week and time of admission on patients' mortality from unplanned admissions, reported in (Bankart et al, 2011;Arulkumaran Harrison and Brett, 2016;Ismail et al, 2017). Such demise might result from other risk factors (such as; inadequate hospital staffing), because there were more hospital presentations than available healthcare staff.…”
Section: Clinical Effectmentioning
confidence: 88%
“…In Scotland, male sex was reported to be associated with NeHA, which might be as a result of the propensity of men to multiple prescriptions, according to . However, another study who investigated three different sites reported female sex to be associated with NeHA; an implication of which revealed lack of hospital facility as a limiting factor for those patients, reported by (Ismail et al 2017). These shortages, might be peculiar to the female gynaecology ED; where medical treatments are focused on female gender.…”
Section: Background Of Studymentioning
confidence: 99%
See 2 more Smart Citations